صيام يوم السبت « دراسة فقهية حديثية - جراية, عماد (جامعة الوادي University of Eloued, 2017)
يعالج هذا الموضوع مسألة"صيام يوم السبت"؛ حيث عرض في البداية ببيان محل النزاع بدقة احترازا من الخروج عن موضع النزاع ومن طرق الموضوع في غير محله، وبالتالي تبديد جهد البحث؛ فأظهر بأن موضع الخلاف هو اختلافهم في جواز صيام يوم السبت في غير الفريضة إذا أفرد، ثم ذكر خلاف أهل العلم في المسألة على قولين: الجواز مطلقا، والقول بالكراهة، ثم ألمح إلى سبب خلافهم، بعدها ذكر الأدلة ومناقشتها ثم خلص إلى ترجيح القول بالجواز، وأظهرت ضعف الخلاف الحاصل في المسألة. ABSTRACT: This research deals with the issue of "fasting on Saturday It aims at clarifying the different opinions regarding the permissibility of fasting on Saturday , on non-obligatory occasions. I mention the different views of the scholars on the matter, with an explanation of the reasons for this discrepancy. The research concluded by saying that it is permitted to fast on Saturday.
fasting On Saturday - Study In Fiqh And Hadith
Keywords: السبت- الصيام- الخلاف- الفقه; Saturday – fasting - Fiqh – disagreement